2023
DOI: 10.3389/frqst.2023.1134583
|View full text |Cite
|
Sign up to set email alerts
|

Quantum non-Markovianity: Overview and recent developments

Abstract: In the current era of noisy intermediate-scale quantum (NISQ) devices, research on the theory of open system dynamics has a crucial role to play. In particular, understanding and quantifying memory effects in quantum systems is critical to gain a better handle on the effects of noise in quantum devices. The main focus of this review is to address the fundamental question of defining and characterizing such memory effects—broadly referred to as quantum non-Markovianity—utilizing various approaches. We first dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 152 publications
0
3
1
Order By: Relevance
“…For example, Ref. [95] showed that the absence of backflow of information in terms of mutual information is equivalent to the "CP-ness" of Φ, but we note that this contradicts some later works [99],…”
Section: Comments On Definition Of Non-markovianitycontrasting
confidence: 81%
See 2 more Smart Citations
“…For example, Ref. [95] showed that the absence of backflow of information in terms of mutual information is equivalent to the "CP-ness" of Φ, but we note that this contradicts some later works [99],…”
Section: Comments On Definition Of Non-markovianitycontrasting
confidence: 81%
“…In our work, we do not consider these operational definitions of non-Markovianity, and will stick to the conventional CP-divisibility definition, also known as the RHP definition, named after Rivas, Huelga, and Plenio [84] (we refer the reader to Ref. [99] for a review of these operational definitions of non-Markovianity).…”
Section: Comments On Definition Of Non-markovianitymentioning
confidence: 99%
See 1 more Smart Citation
“…Markovian evolutions have divisible dynamical maps, allowing for the representation of evolution in a series of continuous steps. Non-Markovianity arises when the dynamical map is not divisible, indicating interruptions or non-continuous evolution [34]. An important measure is given by the Fisher information flow [35][36][37].…”
Section: Introductionmentioning
confidence: 99%